Trade Restrictiveness in the CEMAC Region : The Case of Congo - Oliva, Maria-Angels (IMF Working Papers; Working Paper, 2008)
Congo's vital dependence on trade for development stands in contradiction with its trade policy. As a member of the CEMAC, Congo's tariff scheme at least formally is guided by CEMAC's 1994 trade regime agreement. This paper shows CEMAC's customs code is restrictive relative to that of comparable regional integration groups. The paper also discusses a number of quantitative and qualitative barriers to trade applied by Congo that render its current regime complex, nontransparent, and relatively unpredictable, compromising efforts to develop the non-oil sector and the country's export base. Moreover, Congo's high tariffs and other taxes have not led to higher fiscal revenues, as the number of exemptions granted in recent years has surged and customs administration remains weak.